RIJOQ: VOCAL MUSIC OF DAYAK BENUAQ FROM KUTAI, EAST KALIMANTAN - -, Ester; Listya, Agastya Rama (Harmonia: Journal of Arts Research and Education, 2014)
Rijoq, a Dayak Benuaq vocal music, has been passed down from generation to generation through oral tradition for hundreds of years. When and how it was founded, developed and preserved in the Dayak community remains questionable. But according to some research done by scholars, Rijoq has its origin from Dayak Bawo, a tribe living in the borderlines between Central, South, and East Kalimantan. Rijoq is normally performed during festivities, such as: initiation, reconciliation, menugal (rice planting) and potong kerbau (buffalo slaughtering). Rijoqâs texts have very deep messages which are considered still relevant to todayâs life context. On the one hand, it speaks about the horizontal relationshipâhuman beings and their fellows, and human beings and its natureâ; and on the other hand, the vertical relationshipâhuman beings with their Creator. The primary concern of doing this research is to preserve Rijoq as written and recorded documents. So far, this research has been successful in notating and recording five kinds of Rijoq, that is Peket Muat Bolupm (working together to build lives), Rijoq Patuk Ajer (advice), Rijoq Natal Tautn Bayuq (Christmas and New Year), Rijoq Isiq Asekng Sookng Bawe (the expression of a manâs feeling who is falling in love with a woman), and Rijoq Lati Tana Orekng Tepa (forests and lands are disappearing and gone). But this paper is not intended to discuss these five kinds of Rijoq. Isiq Asekng Sookng Bawe is chosen as it is the oldest and the most difficult Rijoq among the rest.